Role of Herbomineral Drugs in the Management of Diarrhea and Late Effects of Chemotherapy in the Patient of Oral Cavity Cancer - Pankaj Kumar Singh; Sujeet Kumar (AYUSHDHARA, 2025)
Cancer is a state of uncontrolled proliferation of cells that leads to various types of malignancies. It is a type of non-communicable disease that causes millions of deaths every year. For the management of cancer various types of surgical and nonsurgical intervention are practiced. Chemotherapy is the widely used nonsurgical intervention for the management of cancer. After chemotherapy side effects like diarrhea/constipation, hair loss, nausea, vomiting, fatigue etc are seen in patients. Side effects of chemotherapy include damage to rapidly growing cells of body such as mucosal lining from mouth to the gastrointestinal tract. Damage to gastrointestinal mucosal lining due to drugs used in chemotherapy, surface area available for nutrient and water absorption significantly reduced. Patients suffer with recurrent diarrhea due to toxicity of chemotherapeutic drugs on GIT. In modern medicine some selected drugs are used to treat the chemotherapy induced diarrhea (CID). In Ayurvedic texts Atisaar is elaborately discussed by Acharyas which closely resembles diarrhea. Treatment of chemotherapy induced diarrhea by using Ayurvedic medicines is much effective and less costly. In Ayurveda, herbomineral medicines are used to treat diarrhea (Atisaar). In present study some herbomineral drugs used in a patient suffering from diarrhea and late effects of chemotherapy and result was enthusiastic.